ACO based embedded system testing using UML Activity Diagram - Panthi, Vikas; Mohapatra, Durga Prasad (TENCON ... IEEE Region Ten Conference, 2016)
This paper proposed a model-based technique for test scenario generation using Activity Diagram (AD). We transform an AD specification into an intermediate graph called Activity Interaction Graph (AIG) using the proposed parser. After that, we apply combination of BFS and DFS algorithms for generating test scenarios. Then, we apply an algorithm called ACOToTSP (Ant Colony Optimization for Test Scenarios Prioritization) algorithm on the generated test scenarios with respect to some decision and concurrent criteria, for prioritizing the test scenarios. This approach generates test scenarios according to forks, Joins, and merge point's strength in the activity diagram.